2010
DOI: 10.1121/1.3458853
|View full text |Cite
|
Sign up to set email alerts
|

MP3 player listening habits of 17 to 23 year old university students

Abstract: This study evaluated the potential risk to hearing associated with the use of portable digital audio players. Twenty-eight university students (12 males, 16 females; aged 17-23) completed a 49-item questionnaire assessing user listening habits and subjective measures of hearing health. Sound level measurements of participants' self-identified typical and 'worst case' volume levels were taken in different classrooms with background sound levels between 43 and 52 dBA. The median frequency and duration of use was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 17 publications
9
39
1
2
Order By: Relevance
“…For example, Vogel et al (2010) reports that males are more likely to select higher PLLs than females, which is supported by McNeill et al (2010) reporting male PLLs to be a median of 7dBA higher than those of females. Le Prell et al (2011) also found that males using PLDs had significantly elevated hearing thresholds compared to females.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…For example, Vogel et al (2010) reports that males are more likely to select higher PLLs than females, which is supported by McNeill et al (2010) reporting male PLLs to be a median of 7dBA higher than those of females. Le Prell et al (2011) also found that males using PLDs had significantly elevated hearing thresholds compared to females.…”
Section: Discussionsupporting
confidence: 49%
“…Additionally, the other possible influential factor appears to be gender differences for both PLLs and durations of use (Le Prell et al, 2011, Vogel et al, 2010, McNeill et al, 2010. For example, Vogel et al (2010) reports that males are more likely to select higher PLLs than females, which is supported by McNeill et al (2010) reporting male PLLs to be a median of 7dBA higher than those of females.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Hearing loss caused by leisure activities with loud noise has been growing substantially in young populations (1,2,3) , causing concern among researchers (3,4,5,6,7,8) . Exposure to high sound pressure levels in leisure activities has been placing at risk the hearing of young individuals throughout the world.…”
Section: Introductionmentioning
confidence: 99%